The Influence of E-Service Quality And Perceived Value on Customer Loyalty Through E-Trust And Customer Satisfaction In The Klik Indomaret Application - Ghasani Rahman, Navira; Millanyani, Heppy (International Journal of Science, Technology & Management, 2025)
The rise of digital technology has fueled the growth of e-commerce in Indonesia, including mobile apps like Klik Indomaret, a digital platform by one of the country’s largest minimarket chains. Despite its convenience and user-friendly features, Klik Indomaret struggles with customer loyalty, as seen in moderate app ratings and mixed reviews. While previous studies show that e-service quality, perceived value, and e-trust can enhance satisfaction and loyalty, this relationship isn’t always consistent in practice. This study investigates the impact of e-service quality and perceived value on customer loyalty, with e-trust and satisfaction as mediating variables. Using a quantitative approach and PLS-SEM analysis of survey data from Klik Indomaret users, the research offers insights into digital consumer behavior and provides strategic recommendations for improving customer retention.